American Arcadia : California and the classical tradition - Holliday, Peter J. (Oxford University Press, 2016)
Discussing the influence of the classics on America is nothing new; indeed, classical antiquity could be considered second only to Christianity as a force in modeling America's national identity. What has never been explored is how, from the beginning, Californians in particular chose to visually and culturally craft their new world using the rhetoric of classical antiquity. Through a lively exploration of material culture, literature, and architecture, 'American Arcadia' provides a tour through California's development as a Mediterranean haven from the late 19th century to the present